The relationship between work environment and job satisfaction among staff at Pejabat Tanah and Jajahan Pasir Puteh, Kelantan / Siti Mariani Muhamad Ayub - Muhamad Ayub, Siti Mariani (2014)
The purpose of this study is to identify the relationship between work environment and job satisfaction between staff at Pejabat tanah and jajahan Pasir Puteh. The scope of this study is determining the relationship work environment between job satisfactions. Besides that, this study also focused on work environment, physical setting, and healthy environment that can influence job satisfaction. This study uses structure questionnaire method in order to elicit the feedback from employees regarding the purpose of this study. Moreover, this study has used simple random sampling and has chosen 40 respondents out of 45. For recommendation, to increase the job satisfaction among the staff, organization should do the 360 degree feedback to collect all information from employees. Besides that, organization should provide the work environment more safety and comfortable to employees.